2017
DOI: 10.1111/nyas.13346
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of tight junction proteins and the regulation of degradation and recycling

Abstract: Internalization of tight junction (TJ) proteins from the plasma membrane is a pivotal mechanism regulating TJ plasticity and function in both epithelial and endothelial barrier tissues. Once internalized, the TJ proteins enter complex vesicular machinery, where further trafficking is directly dependent on the initiating stimulus and downstream signaling pathways that regulate the sorting and destiny of TJ proteins, as well as on cell and barrier responses. The destiny of internalized TJ proteins is recycling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 117 publications
(297 reference statements)
2
69
0
1
Order By: Relevance
“…Although the underlying intestinal layers may not appear exposed to luminal contents since the mucosa is no longer denuded, the unrestricted permeability pathway via poorly formed tight junctions allows for microorganisms and macromolecules to cross the epithelial barrier. In order for the tight junction barrier and cell polarity to be restored, tight junction proteins internalized during injury, such as the endocytosis of occludin that accompanies anoxic injury in Caco-2 cells, must be reinserted back into the membrane via recycling endosomes [51][52][53]. Ultimately, following these acute repair mechanisms, crypt cells can proliferate and differentiate to restore the proper number of epithelial cells to the monolayer in order to regain full homeostatic function.…”
Section: Acute Mechanisms Of Repair In Injured Intestinal Epitheliummentioning
confidence: 99%
“…Although the underlying intestinal layers may not appear exposed to luminal contents since the mucosa is no longer denuded, the unrestricted permeability pathway via poorly formed tight junctions allows for microorganisms and macromolecules to cross the epithelial barrier. In order for the tight junction barrier and cell polarity to be restored, tight junction proteins internalized during injury, such as the endocytosis of occludin that accompanies anoxic injury in Caco-2 cells, must be reinserted back into the membrane via recycling endosomes [51][52][53]. Ultimately, following these acute repair mechanisms, crypt cells can proliferate and differentiate to restore the proper number of epithelial cells to the monolayer in order to regain full homeostatic function.…”
Section: Acute Mechanisms Of Repair In Injured Intestinal Epitheliummentioning
confidence: 99%
“…The unique pinocytosis process of forming membrane extension or ru es as a result of cytoskeleton reorganization is macropinocytosis. As a consequence of these membrane changes the large amount of extracellular fluid with dissolved molecules is collected, regardless of the presence of any specific receptors [68,69]. Luther et al showed that Fe NPs were successfully taken up by microglial cells chiefly through macropinocytosis and clathrin-mediated endocytosis, in the course of which absorbed particles were directed into the lysosomal compartment [70].…”
Section: Cellular Uptakementioning
confidence: 99%
“…However, on the basis of other reports, we have a few speculations or theories. First, internalization or endocytosis of TJ molecules [32]-the mechanisms of endocytosis and triggered signaling pathways following endocytosis are rather complicated. The process of endocytosis results in changes to the barrier function and plasticity of TJ molecules.…”
Section: Discussionmentioning
confidence: 99%